Political Philosophy & Theology: George Grant, Leo Strauss and the Priority of Love - Athanasiadis, Harris (Toronto journal of theology, 2004)
This essay is about George Grant and his relationship to the political philosopher Leo Strauss. Many will know George Grant as a significant political philosopher in his own right, and one who was uniquely Canadian. Many will have read or heard his sweeping criticism of globalization through technology and his concern over the increasing tyranny such globalization was imposing on the diversity and otherness of life, forcing large-scale conformity toward cultural sameness of the most shallow variety. Many will have read or heard his lament over the loss of what is noble, good and worthy of love and pursuit in the more primal and ancient traditions over against the individual consumerism and aggressive militaristic and corporate domination of the powerful imposed by globalization through technology. Yes indeed, Grant was one of those unique and somewhat rare prophetic voices of Canada. We need to be attentive to his voice if we hope to resist what many of us witness as the tyranny of a relentless necessity toward globalization.